Work-based learning in US higher education policy - Joseph A. Raelin (Higher Education, Skills and Work-Based Learning, 2011)
The purpose of this paper is to discuss how US institutions of higher education make appreciable use of work-based learning options, but their attention to experiential education as a learning vehicle is relatively limited. The connection between the work experience and the on-campus curriculum is only loosely formed, and students are not often given a chance to reflect concurrently and collectively on their workplace lessons. Some changes in higher educational policy have been initiated to augment the pedagogical contribution of a work-based learning, but notable institutional barriers remain. Design/methodology/approach Essay based on policy and literature review. Findings Work-based learning epistemology has demonstrated that knowledge may be equally, if not even more effectively, acquired through reflective discourse within the very activity of practice. Aside from discourse's lens into social structure, it can also be used as a means to expand knowledge for improved action in the world. Research limitations/implications Students make sense out of their workplace experiences and construct knowledge through a process of negotiation between these experiences and their own cognitive frameworks. Originality/value Students learn by doing real work that is often designed to support and integrate with learning in the classroom and also to promote the acquisition of broad transferable skills. The paper shows that by equipping young adults with work-related skills, work-based learning promotes a high level of work role identification and efficacy, which in turn positively influences their successful transition into the work environment.
Keywords: H52; I20; I21; I28; I29; L31; M53; O15; 330; Work-based learning; Higher education; Experiential learning; Reflective practice; Epistemology